Determinant Factors Customer Satisfaction and its Implication on Customer Loyalty: From the Perspective of Customers of Vespa - Tannady, Hendy; Purnamaningsih, Purnamaningsih (International Journal of Science, Technology & Management, 2023)
This study intends to examine the relationship between brand equity, product quality, and service quality, as well as their partial and simultaneous effects on consumer satisfaction and loyalty. Path analysis is the data processing technique employed by researchers. 100 Vespa customers served as the sample for this study's respondents. Primary data were gathered as a consequence of respondents' responses to the questionnaires that were sent out. According to the findings from the first equation, brand equity, product quality, and service quality all have a simultaneous and partial impact on customer happiness. According to the study's findings, the variables of product quality, service quality, brand equity, and customer happiness have a simultaneous and partial impact on customer loyalty based on the second equation.